Morphometric assessment of a population of Araucanian creole pigs (Colombia) - Salamanca-Carreño, Arcesio (2022)
The morphometry is a tool to quantify and analyze morphological variation in the size and shape of animals. The aim of this study was to contribute to the morphometric characterization of the Araucanian creole pig to know some of its functional and ethnological characteristics. For this. 58 pigs (27 females and 31 males), aged between 4 and 48 months, located in three villages of Arauca, eastern Colombia, were studied. Eleven individual body measurements were obtained, and three indices were constructed. Descriptive statistics and univariate analysis were applied to measure the environmental effect on body measurements and indices, using age as a covariate. The pigs showed a medium variability in body measurements associated with a medium harmony. These animals are considered to be dolichocephalic, mesolineal and not suitable for meat purposes. The females tended to be larger than the males. The village was the only effect that influenced the linear combination of the morphological variables and indices. Given the variability of the measurements according to the villages, it could be inferred that different biotypes are present in the Araucanian pigs studied.